Efficacy of Manual Hemostasis for Percutaneous Axillary Artery Intra-Aortic Balloon Pump Removal. (26th July 2020) - Tayal, Rajiv; DiVita, Michael; Sossou, Christoph W.; Okoh, Alexis K.; Stelling, Kelly; McCabe, James M.; Kaki, Amir; Wasty, Najam; Baran, David A.
Abstract : Background . The prevalence of peripheral vascular disease has led to the re-emergence of percutaneous axillary vascular access as a suitable alternative access site to femoral artery. We sought to investigate the efficacy and safety of manual hemostasis in the axillary artery. Methods . Data were collected from a prospective internal registry of patients who had a Maquet® (Rastatt, Germany) Mega 50 cc intra-aortic balloon pumps (IABP) placed in the axillary artery position. They were anticoagulated with weight-based intravenous heparin to maintain an activated partial thromboplastin time (aPTT) of 50–80 seconds. Anticoagulation was discontinued 2 hours prior to the device explantation. Manual compression was used to achieve the hemostasis of the axillary artery. Vascular and bleeding complications attributable to manual hemostasis were classified based on the Valve Academic Research Consortium-2 (VARC-2) and Bleeding Academic Research Consortium-2 (BARC-2) classifications, respectively. Results . 29 of 46 patients (63%) achieved axillary artery homeostasis via manual compression. The median duration of IABP implantation was 12 days (range 1–54 days). Median compression time was 20 minutes (range 5–60 minutes). There were no major vascular or bleeding complications as defined by the VARC-2 and BARC-2 criteria, respectively. Conclusion . Manual compression of the axillary artery appears to be an effective and safe method for achieving hemostasis. Large prospective randomized control trials may be needed to corroborate these findings.